Process evaluation of a supportive intervention targeting social isolation among older people in Danish senior centres: Explanatory factors of implementation failure - Sofie Langergaard; Rhiannon Evans; Jane Andreasen; Kirsten Schultz Petersen; Charlotte Overgaard (PLoS ONE, 2026)
This article explores the implementation of a supportive intervention in Danish municipal senior centres targeting social isolation among older people. The intervention, implemented between April 2022 and April 2023, comprised three key components: a start conversation for all new users; an assigned “buddy” among existing users; and monthly follow-up conversations. Skills development workshops for staff members were held prior to implementation of the intervention. The feasibility evaluation revealed concerns about the intervention implementation. This study describes the low level of implementation and explanatory factors contributing to the failure. We conducted a process evaluation as part of a feasibility evaluation of the intervention. The intervention was implemented in three municipal senior centres, ten senior centre staff members and 18 senior centre users participated. Data collection involved 23 semi-structured interviews with users and staff. Thematic analysis was conducted. Results are presented in two parts: 1) Overview of implemented components showing a low degree of fidelity in implementation, 2) Explanatory factors influencing implementation. The three factors identified were: A “too” systematic approach; Navigating frailty; and Lack of integration. These factors resulted in challenges recruiting participants and issues with performing some of the intervention elements. This evaluation provides insights into delivering interventions in municipal senior centres, emphasising explanatory factors to avoid implementation failures. The findings can support future development of contextually responsive interventions that can function as intended when delivered in real-world settings.